Effects of Oligosaccharides From Morinda officinalis on Gut Microbiota and Metabolome of APP/PS1 Transgenic Mice - Xin, Yang; Diling, Chen; Jian, Yang; Ting, Liu; Guoyan, Hu; Hualun, Liang; Xiaocui, Tang; Guoxiao, Lai; Ou, Shuai; Chaoqun, Zheng; Jun, Zhao; Yizhen, Xie (Frontiers in Neurology, 2018)
Alzheimer’s disease (AD), a progressive neurodegenerative disorder, lacks preclinical diagnostic biomarkers and therapeutic drugs. Thus, earlier intervention in AD is a top priority. Studies have shown that the gut microbiota influences central nervous system disorders and that prebiotics can improve the cognition of hosts with AD, but these effects are not well understood. Preliminary research has shown that oligosaccharides from Morinda officinalis (OMO) are a useful prebiotic and cause substantial memory improvements in animal models of AD; however, the mechanism is still unclear. Therefore, this study was conducted to investigate whether OMO are clinically effective in alleviating AD by improving gut microbiota. OMO were administered to APP/PS1 transgenic mice, and potential clinical biomarkers of AD were identified with metabolomics and bioinformatics. Behavioral experiments demonstrated that OMO significantly ameliorated the memory of the AD animal model. Histological changes indicated that OMO ameliorated brain tissue swelling and neuronal apoptosis and downregulated the expression of the intracellular AD marker Aβ1-42. 16S rRNA sequencing analyses indicated that OMO maintained the diversity and stability of the microbial community. The data also indicated that OMO are an efficacious prebiotic in an animal model of AD, regulating the composition and metabolism of the gut microbiota. Serum metabolomic analysis by UHPLC-LTQ Orbitrap mass spectrometry was performed to identify the metabolic changes and potential early biomarkers in APP/PS1 transgenic mice. Multivariate statistical analysis revealed that 14 metabolites were significantly up-regulated and 8 were down-regulated in the model compared with normal mice. This study revealed that key metabolites provide an early indicator of AD incidence. Overall, we have identified a drug and several signaling pathways with therapeutic potential, including proteins associated with cognitive deficits in normal mice and gene mutations that cause AD.